THE EFFECTIVENESS OF DISPUTE SETTLEMENT ON THE RESULT OF PRESIDENTIAL ELECTION 2014 IN THE CONSTITUTIONAL COURT - Muhammad Soni (FH 15 UMY 137, 2016)

(untitled)
*137 The Constitutional Court has rejected the petition of Prabowo Subianto-Hatta Rajasa in the disputes on the result of Presidential Election 2014. The reason of rejaction was because the Court considered that the petitioners failed in providing a story evidence in supporting their claim in the petition. The failure of petitioners in providing evidence was also influenced by limitation of period of disputes settlement in the Constitutional Court, that is only 14 days. In addition, the Court also limited the number of witnesses proposed by the petitioners. Therefore, it seems that is has put the petitioners in difficult position in defending their right in the process of Presidential Election. Keyword: Constitutional Court, Presidential Election.